EVALUATION OF PROFESSIONAL ETHICS AND ETHICAL THEORY IN MANAGERIAL PRACTICE GARUDA INDONESIA CASE STUDY 2019 - Dito Aditya Darma Nst; Diana Trisisca; Chandra Prayoga; Siti Rana Aqilah; Fahradilla Aulia; Ario Anggoro; Heru Syahputra (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Professional ethics is crucial for the workplace, especially for managers who play a strategic role in decision-making and organizational policies. In analyzing professional ethics for decision-making purposes, this article focuses on professional ethics theories, professional ethics principles, and a case study at PT. Garuda Indonesia. The case study discussed includes the manipulation of the 2018 financial statements related to the implementation of ethics and internal management awareness. The analysis used in this article is utilitarianism, deontology, and welfare ethics, where PT. Garuda Indonesia's management failed to meet applicable moral standards. The findings of this study indicate that integrity, responsibility, and organizational culture are important components that must be upheld in business.